A subaquatic moraine complex in overdeepened Lake Thun (Switzerland) unravelling the deglaciation history of the Aare Glacier. (1st May 2018) - Fabbri, S.C.; Buechi, M.W.; Horstmeyer, H.; Hilbe, M.; Hübscher, C.; Schmelzbach, C.; Weiss, B.; Anselmetti, F.S.
Abstract: To investigate the history of the Aare Glacier and its overdeepened valley, a high-resolution multibeam bathymetric dataset and a 2D multi-channel reflection seismic dataset were acquired on perialpine Lake Thun (Switzerland). The overdeepened basin was formed by a combination of tectonically predefined weak zones and glacial erosion during several glacial cycles. In the deepest region of the basin, top of bedrock lies at ∼200 m below sea level, implying more than 750 m of overdeepening with respect to the current fluvial base level (i.e. lake level). Seismic stratigraphic analysis reveals the evolution of the basin and indicates a subaquatic moraine complex marked by high-amplitude reflections below the outermost edge of a morphologically distinct platform in the southeastern part of the lake. This stack of seven subaquatic terminal moraine crests was created by a fluctuating, "quasi-stagnant" grounded Aare Glacier during its overall recessional phase. Single packages of overridden moraine crests are seismically distuinguishable, which show a transition downstream into prograding clinoforms with foresets at the ice-distal slope. The succession of subaquatic glacial sequences (foresets and adjacent bottomsets) represent one fifth of the entire sedimentary thickness. Exact time constraints concerning the deglacial history of the Aare Glacier are very sparse. However, existing 10 Be exposure ages from the accumulation area of the Aare Glacier and radiocarbon ages from a Late-Glacial lake close to the outlet of Lake Thun indicate that the formation of the subaquatic moraine complex and the associated sedimentary infill must have occurred in less than 1000 years, implying high sedimentation rates and rapid disintegration of the glacier. These new data improve our comprehension of the landforms associated with the ice-contact zone in water, the facies architecture of the sub- to proglacial units, the related depositional processes, and thus the retreat mechanisms of the Aare Glacier. Highlights: The overdeepening of the perialpine Aare Valley reaches down to −220 m a.s.l. A subaquatic moraine complex marks a short dramatic halt during LGM deglaciation. The complex was built in <1000 years with sedimentation rates >8 cm/yr.